Highly bioavailable curcumin preparation with a co‐grinding and solvent‐free process. Issue 12 (7th October 2020) - Lu, Yiying; Lin, Mengting; Zong, Jiancheng; Zong, Lei; Zhao, Zhen; Wang, Shanglong; Zhang, Zengliang; Han, Min
Abstract: Curcumin (Cur.) is a natural product isolated from the rhizome of Curcuma longa, with a variety of biological and pharmacological activities in food and pharmaceutical products. However, curcumin's poor solubility in water greatly limits its bioavailability and clinical applications. In this study, co‐grinding curcumin with food additives produced a mixture, which was evaluated for the solubility in water, dissolution, material morphology, in vivo bioavailability, cell uptake and entry mechanism. We tested 9 food additives in total and found that poloxamers performed the best. The 2 co‐grinding mixtures Cur./Kolliphor ® P407 and Cur./Kolliphor ® P188 with high drug loading at 65.5% significantly improved the curcumin aqueous solubility, subsequently increased its intestinal epithelial cell uptake and oral bioavailability. The relative bioavailabilities for the 2 co‐grinding mixtures were 309% and 163%, respectively, compared with curcumin API. Co‐grinding process has a broad application prospect and is suitable for industrial production. Abstract : The 2 co‐grinding mixtures Cur./Kolliphor® P407 and Cur./ Kolliphor® P188 with high drug loading at 65.5% significantly improved the curcumin aqueous solubility and oral bioavailability. The relative bioavailabilities for the 2 co‐grinding mixtures were 309% and 163%, respectively, compared to curcumin API.